The Pharmacist Knowledge and Computer Skills Towards E-Health. Results of A Survey among Italian Community Pharmacists - Iolanda, Grappasonni; Seyed, Khosrow Tayebati; Fabio, Petrelli; Francesco, Amenta (Journal of Bioinformatics And Diabetes, 2014)
Background: Health practitioners of different disciplines (physicians, paramedic personnel, pharmacists) should possess adequate ICT (Information and Communication Technology) skills and practical competence on these technologies. Pharmacy practice requires a relevant flow of information, collection and handling of which could be facilitated by ICT. The correct use of ICT requires a proper knowledge by professionals offering a public service. The purpose of this paper was to assess basic informatics background and computer uses in pharmacists practicing in Italy, with the aim to identify educational interventions for increasing their informatics abilities. Methods: A questionnaire was proposed to pharmacists working in Italian community pharmacies. The survey was articulated into 35 questions concerning computer basic knowledge, ICT facilities, computer skills, habits, and uses in pharmacy practice. Results: The questionnaire was completed by ~45% (No. 224) of responders, the 96.9% of which used computer. Only 7.8% of interviewed people employed e-mail to communicate with health authorities and less than 2% used it to be in contact with physicians or other health professionals. Less than 40% used ICT for training courses. The results revealed a relevant percentage (90.8%) of self-learners to computer use, while only 9.2% was trained by specific courses. Conclusion: Basic knowledge of community pharmacists on ICT technological infrastructure is quite low. Although pharmacists play an essential role in health services, they have apparently limited computer skills. This suggests the need of educational and training efforts for enlarging computer and ICT resources competent use in daily pharmacy practice.
Keywords: Pharmacists; Public Health; Professional development; Computer skills; Education.